DIFFERENCES IN EXAMINATION OF USUS NEMATODE EGGS ON FESES BETWEEN FLOTATION METHODS AND SEDIMENTATION METHODS FOR STUDENTS AT SDN 11 TELAGA - Dian Putri Muhrija; Agusriyanto Yusuf; Natan Pasiga (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Various types of intestinal worms are still a public health problem and are often found both in cities and in villages in Indonesia, which can lead to anemia, malnutrition, impaired growth and impaired intelligence. This also leads to choosing the right method to determine a person's worm status. The use of a fecal examination method that has a high level of sensitivity and specificity is very important in order to obtain a worm status or accurate results. A person's worms status can be ascertained by finding worm eggs in a fecal laboratory examination. This study aims to determine differences in the results of examining intestinal nematode eggs in feces between Flotation methods and sedimentation methods for students at SDN 11 Telaga. This research is a quantitative analytic comparative method, with a sample size of 35 people from a population of 54 people. The data analysis used is univariate analysis and bivariate analysis. The results were tested with Wilcoxon. The results of this study showed that the flotation method was positive, and in the sedimentation method there were no intestinal nematode eggs.